The ageing mechanism of stored rice: A concept model from the past to the present. (October 2015) - Zhou, Zhongkai; Wang, Xiaofeng; Si, Xu; Blanchard, Chris; Strappe, Padraig
Abstract: Rice ageing is a complicated process. Ageing is unique in rice: no other grains show such behaviors. More recent years, novel techniques, such as HS-SPME–GC–MS and e-nose system were used to monitor rice ageing process. Storage conditions were also investigated for minimizing rice ageing process, and the literature indicated hermetic storage could significantly improve overall paddy quality, with providing a more practical and useful method for maintaining rice quality and controlling insect mortality during rice storage. Although there were no significant differences in the gross contents of starch, cell wall remnants, proteins and lipids, the ageing process did cause a shift in the components of a number of chemical groupings. Studies also showed that the interactions among macro- and micro-compositions in rice grains during storage would play key roles on the changes of rice overall physicochemical and cooking properties. Based on recent years' studies, a conceptual model for interpreting rice ageing mechanism is proposed. Highlights: Specific storage conditions could maintain rice quality and control insect mortality during storage. Changes in rice physicochemical property are induced mainly from non-starch components. Ageing process leads to rice becoming progressively organized and reinforced. Conceptual model of rice ageing at a cellular and molecular level is proposed.